Measurement of the average very forward energy as a function of the track multiplicity at central pseudorapidities in proton-proton collisions at root s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Bergauer, Thomas; Md. Ali, Mohd. Adli (Springer Nature, 2019)
e average total energy as well as its hadronic and electromagnetic components are measured with the CMS detector at pseudorapidities −6.6 <η< −5.2 in protonproton collisions at a centre-of-mass energy √s = 13 TeV. The results are presented as a function of the charged particle multiplicity in the region |η| < 2. This measurement is sensitive to correlations induced by the underlying event structure over a very wide pseudorapidity region. The predictions of Monte Carlo event generators commonly used in collider experiments and ultra-high energy cosmic ray physics are compared to the data. All generators considered overestimate the fraction of energy going into hadrons.